EFEKTIVITAS PERANAN BPOM DALAM PENGAWASAN PEREDARAN KOSMETIK ILEGALDI KOTA DENPASAR - Aryantini, Ni Putu Devi; Ratih Kumala Dewi, Ni Komang (Jurnal Hukum Mahasiswa, 2024)
The rampant circulation of illegal cosmetics certainly raises anxiety for the public and the cosmetics industry in Indonesia in general and in Denpasar City in particular, Anticipating this, the government has formed the Food and Drug Supervisory Agency (BPOM). BPOM has an important role in overseeing the circulation of illegal cosmetics as regulated in the Regulation of the Head of theFood and Drug Supervisory Agency, besides that BPOM was formed to detect,prevent and supervise products including to protect security and safety and publichealth. Based on the facts as described above, the author is interested in conducting a study on the effectiveness of the role of BPOM in monitoring thecirculation of illegal cosmetics in Denpasar City. The research method used by theauthor is empirical research method. BPOM in supervising the circulation of illegalcosmetics in Denpasar City has been running in accordance with applicable regulations and BPOM has effectively supervised the circulation of illegal cosmeticsin Denpasar even though in conducting BPOM supervision it also experiences various obstacles including law enforcement factors, facilities and infrastructurefactors, and community factors.